STRATEGI PEMASARAN IKAN NILA HASIL BUDIDAYA KERAMBA JARING APUNG PADA KELOMPOK POKDAKAN PEMUDA KBR TENGGARONG - Gunawan, Andri; Wijayanti, Silvana Kardinar; Fahleti, Widya Hana (SEKOLAH TINGGI ILMU EKONOMI TENGGARONG, 2022)
This study aims to find out what marketing strategies are effective for increasing sales of tilapia from floating net cage cultivation in the KBR Youth Pokdakan Group through SWOT analysis. This study uses a qualitative research type. Primary data was collected through interviews with several stakeholders of the KBR Youth Pokdakan Group, namely Mr. Susanto (Chairman of the KBR Youth Pokdakan Group), Mr. Subli (Secretary of the KBR Youth Pokdakan Group), Mr. Doni (Marketing Section of the KBR Youth Pokdakan Group). In addition to the interview method, the author also uses the observation method to deepen the data obtained. Secondary data was obtained through a literature study from the KBR Youth Pokdakan Group and the author's documentation. The data that has been collected is then analyzed using the SWOT method.